Influence of the duration of aging the system Ti/Al2O3 in a hydrogen atmosphere on hydrogen sorption, adhesion, tribology, and electrical conductivity of the film - Sypchenko, Vladimir; Kiselyova, Evgeniya; Sigfusson, Thorstein; Lisichko, Elena; Semkina, Ludmila; Efremova, Natalya; Rudkovskaya, Vera (Eastern-European Journal of Enterprise Technologies, 2018)
This paper reports results on the interaction between an aluminum oxide film, deposited on technically pure titanium of grade VT1-0 by the magnetron reactive sputtering method, and a hydrogen-containing atmosphere. Such a study is important in order to find protective coatings that would prevent the penetration of hydrogen inside a product. A given system aged in a hydrogen atmosphere in the interval of 1‒4 hours at a pressure of 2∙105 Pa (2 bar) and a temperature of 400 °C. We have acquired data on the distribution of hydrogen along a film thickness and its content in a thin-film system. It is shown that hydrogen diffuses into the film and builds up in it up to three hours, and only then it begins to penetrate the substrate. We have managed to increase aging duration in a hydrogen-containing environment and increase the temperature of heating up to the stage of film destruction. In the case of the starting film and after aging from 1 to 3 hours the adhesion force between a film and a substrate increases, apparently due to the formation of hydrogen bonds film-substrate. The adsorption of hydrogen atoms at the surface of the Al2О3 film is accompanied by an increase in its conductivity by not larger than 4 % with the increased time of aging. Such a change in the conductivity of the Al2О3 film can be explained based on the formation of a zone structure. Thin oxide films may possess continuous one-side conductivity, but in the case the film is thick (0.5 µm and above), it is not possible to argue about the one-side conductivity. The data acquired on the influence of aging duration in a hydrogen atmosphere indicate an increase in adhesive strength by almost 6 times within 3 hours and by 2.5 times in 4 hours. The determined coefficient of film friction increases by not larger than 2.5 times. By measuring the electrical conductivity of the film surface, it was found that it increases with an increase in the time of aging in a hydrogen atmosphere. This pattern is obviously linked to the creation of transitions of the p-n-type in the film of aluminum oxide at the expense of hydrogen ions